2008
DOI: 10.1037/0882-7974.23.2.287
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism moderates the daily relation between stressors and memory failures.

Abstract: The present investigation extends previous work on the relationship between daily stressors and memory failures in a naturalistic setting by examining whether this relationship varies across levels of neuroticism. A daily diary study of 333 older adults (mean age = 73.27 years, SD = 7.17) in the Veterans Affairs Normative Aging Study (see A. Spiro & R. Bossé, 2001, for additional information) was used to examine whether there were neuroticism differences in cognitive reactivity to daily stressors. Multilevel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 86 publications
(121 reference statements)
1
51
1
1
Order By: Relevance
“…This semi-structured inventory possesses construct validity; stressor content and focus variables accounting for 8% of the variance in physical symptoms and 12% of variance in negative mood (Almeida et al, 2002). This paper-pencil version of the DISE has been used with previous results from the NAS diary data (e.g., Neupert et al, 2006; Neupert et al, 2008) as well as other daily diary studies (e.g., Neupert, Ennis, Ramsey, & Gall, 2015). Participants respond yes or no to whether arguments, potential arguments, work or volunteer setting stressors, home stressors, network stressors, health stressors, and other stressors occurred each day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This semi-structured inventory possesses construct validity; stressor content and focus variables accounting for 8% of the variance in physical symptoms and 12% of variance in negative mood (Almeida et al, 2002). This paper-pencil version of the DISE has been used with previous results from the NAS diary data (e.g., Neupert et al, 2006; Neupert et al, 2008) as well as other daily diary studies (e.g., Neupert, Ennis, Ramsey, & Gall, 2015). Participants respond yes or no to whether arguments, potential arguments, work or volunteer setting stressors, home stressors, network stressors, health stressors, and other stressors occurred each day.…”
Section: Methodsmentioning
confidence: 99%
“…These positive emotions may serve to dampen the detrimental effects of the negative emotions on reactivity to stressful situations (Levenson, 1999). In line with previous studies (e.g., Almeida, 2005; Neupert, Mrozcek, & Spiro, 2008), reactivity is operationalized as the within-person relationship between a stressor and a given outcome. It follows then, that individuals with higher levels of co-occurrence of affect could show less reactivity in response to daily stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Such a disposition (typically characterized as neuroticism , as we will detail in the following text) may exacerbate the damaging effects of stress on cognition. Neupert, Mroczek, and Spiro (2008) analyzed diary reports of participants from the Normative Aging Study over 8 days and found that reports of stress were coupled with reports of memory failures, but that this effect was heightened for those higher in neuroticism.…”
Section: Manage Stressmentioning
confidence: 98%
“…Nörotik bireylerin yaşamları boyunca olumsuz duygulanımlar tecrübe etmeye meyilli oldukları, olayların olumsuz yönlerine odaklandıkları (Hemenover, 1996) stres verici olaylara aşırı duyarlılık gösterdikleri, stres yaratan olayları daha olumsuz algıladıkları ve stres verici olaylarla karşılaştıklarında daha olumsuz tepkiler verdikleri araştırmalarca ortaya konan bir bulgudur (Neupert, Mroczek ve Spiro, 2008). Stres verici olayların gerçekçi olmayacak ölçüde tehditkâr olarak algılanması ve olumsuz bir şekilde anlamlandırılması sonucu onlardan kaçınma ve onları elimine etme davranışlarının artması hem algılanan stres miktarını arttırmakta, hem de stresle etkili bir şekilde başa çıkılmasını zorlaştırmaktadır (Abbasi, 2011).…”
Section: Nörotiklikunclassified